Social Learning Strategies: Bridge-Building between Fields. Issue 7 (July 2018) - Kendal, Rachel L.; Boogert, Neeltje J.; Rendell, Luke; Laland, Kevin N.; Webster, Mike; Jones, Patricia L.
Abstract : While social learning is widespread, indiscriminate copying of others is rarely beneficial. Theory suggests that individuals should be selective in what, when, and whom they copy, by following 'social learning strategies' (SLSs). The SLS concept has stimulated extensive experimental work, integrated theory, and empirical findings, and created impetus to the social learning and cultural evolution fields. However, the SLS concept needs updating to accommodate recent findings that individuals switch between strategies flexibly, that multiple strategies are deployed simultaneously, and that there is no one-to-one correspondence between psychological heuristics deployed and resulting population-level patterns. The field would also benefit from the simultaneous study of mechanism and function. SLSs provide a useful vehicle for bridge-building between cognitive psychology, neuroscience, and evolutionary biology. Highlights: Accumulating evidence supports theoretical predictions that humans and nonhumans are selective in what, when, and whom they copy, suggesting the use of SLSs. Recent studies indicate that SLS use is flexible and changes with ontogeny, experience, state, and context. Multiple SLSs may be adopted simultaneously in the same population, and even by the same individual. The SLSs of individuals do not necessarily correspond to apparent population-level patterns. SLSs likely involve associative learning processes and social learning mechanisms; experimental controls indicate that associative learning alone cannot explain all SLS findings. Recent neuroscientific data suggest that the anterior cingulate cortex in the gyrus (ACCg) is specialised for processing the social information of relevance to SLSs. The role of metacognition in SLSs requires investigation.